The effect of small solar powered 'Bͻkͻͻ' net fans on mosquito net use: results from a randomized controlled cross-over trial in southern Ghana. (December 2017) - Briët, Olivier; Yukich, Joshua; Pfeiffer, Constanze; Miller, William; Jaeger, Mulako; Khanna, Nitin; Oppong, Samuel; Nardini, Peter; Ahorlu, Collins; Keating, Joseph
Abstract Background Long-lasting insecticidal nets (LLINs) are ineffective malaria transmission prevention tools if they are unused. Discomfort due to heat is the most commonly reported reason for not using nets, but this problem is largely unaddressed. With increasing rural electrification and the dropping price of solar power, fans could improve comfort inside nets and be affordable to populations in malaria endemic areas. Here, results are presented from a pilot randomized controlled cross-over study testing the effect of fans on LLIN use. Methods Eighty-three households from two rural communities in Greater Accra, Ghana, randomized into three groups, participated in a 10-month cross-over trial. After a screening survey to identify eligible households, all households received new LLINs. Bͻkͻͻ net fan systems (one fan per member) were given to households in Group 1 and water filters were given to households in Group 2. At mid-point, Group 1 and 2 crossed over interventions. Households in Group 1 and 2 participated in fortnightly surveys on households' practices related to nets, fans and water filters, while households in Group 3 were surveyed only at screening, mid-point and study end. Entomological and weather data were collected throughout the study. Analysis took both 'per protocol' (PP) and 'intention to treat' (ITT) approaches. The mid- and end-point survey data from Group 1 and 2 were analysed using Firth logistic regressions. Fortnightly survey data from all groups were analysed using logistic regressions with random effects. Results Provision of fans to households appeared to increase net use in this study. Although the increase in net use explained by fans was not significant in the primary analyses (ITT odds ratio 3.24, p > 0.01; PP odds ratio = 1.17, p > 0.01), it was significant in secondary PP analysis (odds ratio = 1.95, p < 0.01). Net use was high at screening and even higher after provision of new LLINs and with follow up. Fan use was 90–100% depending on the fortnightly visit. Conclusions This pilot study could not provide definitive evidence that fans increase net use. A larger study with additional statistical power is needed to assess this association across communities with diverse environmental and socio-demographic characteristics.